Phenotypic Timeline Kinetics, Integrative Networks, and Performance of T- and B-Cell Subsets Associated with Distinct Clinical Outcome of Severe COVID-19 Patients - Gabriela de Oliveira; Ismael Artur Costa-Rocha; Nani Oliveira-Carvalho; Tâmilla Mayane Alves Fidelis dos Santos; Ana Carolina Campi-Azevedo; Vanessa Peruhype-Magalhães; Vitor Hugo Simões Miranda; Roberta Oliveira Prado; Agnes Antônia Sampaio Pereira; Clarice Carvalho Alves; Joaquim Pedro Brito-de-Sousa; Laise Rodrigues Reis; et al. (Microorganisms)
The present study aimed to evaluate the kinetics of the phenotypic profile and integrative networks of T/B-cells in severe COVID-19 patients, categorized according to disease outcome, during the circulation of the B.1.1.28 and B.1.1.33 SARS-CoV-2 strains in Brazil. Peripheral blood obtained at distinct time points (baseline/D0; D7; D14-28) was used for ex vivo flow cytometry immunophenotyping. The data demonstrated a decrease at D0 in the frequency of CD3+ T-cells and CD4+ T-cells and an increase in B-cells with mixed activation/exhaustion profiles. Higher changes in B-cell and CD4+ T-cells at D7 were associated with discharge/death outcomes, respectively. Regardless of the lower T/B-cell connectivity at D0, distinct profiles from D7/D14-28 revealed that, while discharge was associated with increasing connectivity for B-cells, CD4+ and CD8+ T-cells death was related to increased connectivity involving B-cells, but with lower connections mediated by CD4+ T-cells. The CD4+CD38+ and CD8+CD69+ subsets accurately classified COVID-19 vs. healthy controls throughout the kinetic analysis. Binary logistic regression identified CD4+CD107a+, CD4+T-bet+, CD8+CD69+, and CD8+T-bet+ at D0 and CD4+CD45RO+CD27+ at D7 as subsets associated with disease outcomes. Results showed that distinct phenotypic timeline kinetics and integrative networks of T/B-cells are associated with COVID-19 outcomes that may subsidize the establishment of applicable biomarkers for clinical/therapeutic monitoring.